Different methods of basic preparation of soil after fish pond on the reclaimed lands of Astrakhan region - A. S. Sokolov; G. F. Sokolova (Овощи России, 2020)
Relevance and methods. The article presents the results of research of various methods of basic soil preparation for melons planting for commercial purposes after a fish pond. The trial scheme covered the study of two variants: dumped tillage single-furrow plow (traditional), used to proceed in the farming unit, and sweep blade tillage with subsurface plow (proposed). In the course of scientific research there were determined agrophysical properties of soil, moisture content, contamination of crops (weediness), yielding capacity and profitability.Results. It was found that the lowest bulk density of soil of 1.12 and 1.15 t/m3 was in the layers of 0.0-0.1 and 0.1-0.2 m after carrying out of the dumped tillage. When carrying out sweep blade tillage, the bulk density of soil of 1.17 t/m3 was obtained only in the upper layer of 0.0-0.1 m, in subsequent layers the value of bulk density of soil significantly increased from 1.44 (0.1-0.2 m) to 1.56 t/m3 (0.3-0.4 m). On average the indicators of natural soil moisture were in 1.2-1.3 times higher, and the deposit of moisture was in 1.1-1.5 times higher in the variant with subsurface plow treatment of the soil. For the melon crops cultivated according to traditional technology, there was a significant decrease in 1.8 times of the number of weeds and in 1.7 -times of their raw weight, compared with the proposed technology. The yielding capacity of melon of Lada variety was 43.9 t/ha according to the traditional technology, and 48.4 t/ha according to the proposed technology, profitability was 161.3% and 185.8% respectively.